Cadmium phosphide as a new material for infrared converters - Stepanchikov, D.; Shutov, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Possible use of cadmium phosphide (Cd₃P₂) for infrared converter systems has been debated. The interband absorption coefficient calculations has been executed for single crystals of n-Cd₃P₂ and interpreted in the exact generalized Kildal band model. Relationship between the absorption coefficient and radiation temperature is presented. On the ground of our calculations, the theoretical temperature dependences of the maximum values of photovoltage and efficiency have been obtained. A common thermo-dynamical approach was applied in this case. The source of radiation was a black body. In our investigations, the barrier structure on metal-semiconductor basis with the Schottky layer has been considered. The operation temperature range for the Me–n-Cd₃P₂ converter has been found.